2022
DOI: 10.3390/dj10060105
|View full text |Cite
|
Sign up to set email alerts
|

Influence on Implant Bone Healing of a Collagen Membrane Placed Subjacent the Sinus Mucosa—A Randomized Clinical Trial on Sinus Floor Elevation

Abstract: Background: Perforation of the sinus mucosa is quite a frequent complication that might occur during sinus floor elevation. The perforation is often protected with a collagen membrane to avoid the extrusion of graft particles within the sinus. However, this procedure might hinder the innate osteogenic potential of the sinus mucosa. Hence, the aim of the study was to evaluate the influence of a placement of a collagen membrane subjacent the Schneiderian membrane during sinus floor elevation on implant bone heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The possibility of analyzing implants retrieved from the human maxilla after bone graft procedures and implant installation has rarely been reported in the literature [6][7][8][9][15][16][17][18][19]. The causes of implant retrieval in humans are usually attributable to implant fractures [15][16][17] or peri-implantitis [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of analyzing implants retrieved from the human maxilla after bone graft procedures and implant installation has rarely been reported in the literature [6][7][8][9][15][16][17][18][19]. The causes of implant retrieval in humans are usually attributable to implant fractures [15][16][17] or peri-implantitis [19].…”
Section: Discussionmentioning
confidence: 99%
“…The histological healing processes of various biomaterials for maxillary sinus floor elevation has been studied [3]. A series of bioptic clinical studies have reported data on the integration of mini-implants installed six months after sinus floor elevation and retrieved three months later [6][7][8][9]. These studies showed a low impact of both dimension and position of the access window on osseointegration.…”
Section: Introductionmentioning
confidence: 99%
“…The second clinical study evaluated the effect on implant osseointegration on a collagen membrane subjacent the sinus mucosa [ 53 ]. Twenty patients participated in this randomized clinical trial.…”
Section: A Synopsis Of the Special-editions Papersmentioning
confidence: 99%